2008
DOI: 10.1002/chem.200800492
|View full text |Cite
|
Sign up to set email alerts
|

Half‐Sandwich Bis(tetramethylaluminate) Complexes of the Rare‐Earth Metals: Synthesis, Structural Chemistry, and Performance in Isoprene Polymerization

Abstract: The protonolysis reaction of [Ln(AlMe(4))(3)] with various substituted cyclopentadienyl derivatives HCp(R) gives access to a series of half-sandwich complexes [Ln(AlMe(4))(2)(Cp(R))]. Whereas bis(tetramethylaluminate) complexes with [1,3-(Me(3)Si)(2)C(5)H(3)] and [C(5)Me(4)SiMe(3)] ancillary ligands form easily at ambient temperature for the entire Ln(III) cation size range (Ln=Lu, Y, Sm, Nd, La), exchange with the less reactive [1,2,4-(Me(3)C)(3)C(5)H(3)] was only obtained at elevated temperatures and for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
81
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 67 publications
14
81
1
3
Order By: Relevance
“…Comparing the performance of 1 with its [AlMe 4 ] analogue [(Tp t Bu,Me )Lu(Me)(AlMe 4 )] ( I Lu ), (Table , runs 10 and 11) revealed that I Lu is only active, when activated by a Brønsted acid, that is, cocatalyst B under the given conditions. Binary system I Lu / B produced polymers with higher trans contents compared to the boryl‐implemented system 1 / B , which is in analogy the polymers fabricated by similar Cp*‐supported systems , . Furthermore, complex [Cp*Lu(AlMe 3 {B(NDippCH) 2 }) 2 ] ( II ) has been investigated previously by us (Table , runs 12–17) .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Comparing the performance of 1 with its [AlMe 4 ] analogue [(Tp t Bu,Me )Lu(Me)(AlMe 4 )] ( I Lu ), (Table , runs 10 and 11) revealed that I Lu is only active, when activated by a Brønsted acid, that is, cocatalyst B under the given conditions. Binary system I Lu / B produced polymers with higher trans contents compared to the boryl‐implemented system 1 / B , which is in analogy the polymers fabricated by similar Cp*‐supported systems , . Furthermore, complex [Cp*Lu(AlMe 3 {B(NDippCH) 2 }) 2 ] ( II ) has been investigated previously by us (Table , runs 12–17) .…”
Section: Resultsmentioning
confidence: 54%
“…Given the importance of organoaluminum cocatalysts in rare‐earth‐metal‐based 1,3‐diene polymerization, we set out to develop a bis(hydrocarbylaluminate) postmetallocene library to better understand any potential Ln–Al bimetallic cooperativity as well as ancillary ligand effects . Initially, we and others introduced half‐sandwich bis(tetramethylaluminate) rare‐earth‐metal complexes of the general type [Cp R₅ Ln(AlMe 4 ) 2 ] [R 5 = HMe 4 , Me 5 , H 2 t Bu 3 , Me 4 SiMe 3 ,, H 3 (SiMe 3 ) 2 , Me 4 (quinolyl), Me 4 ( N , N ‐dimethylanilyl), Me 4 (C 2 H 4 NMe 2 )] as donor‐solvent free derivatives and established them as versatile precatalysts for the synthesis of highly stereoregular polyisoprene, when pretreated with borane/borate cocatalysts (Figure ). Varying the substitution pattern of the cyclopentadienyl (Cp) ligand allowed for a comprehensive assessment of the electronic and steric implications of the ancillary ligand for the catalytic performance ,.…”
Section: Introductionmentioning
confidence: 99%
“…[9, 10] Vorangegangene Untersuchungen unserer Arbeitsgruppe befassten sich mit Seltenerdmetall(III)-TetramethylaluminatKomplexen [L x Ln{Al(CH 3 ) 4 } y ] (y = 1, 2, 3; x + y = 3, L = einzähniger Hilfsligand, Ln = Seltenerdmetall und Sc, Y, La) als Polymerisationskatalysatoren [11,12] und führten zur Isolation von Ln III -Clustern mit Methylen-, [13,14] Methin- [15] und Carbidfunktionalitäten.[ …”
unclassified
“…Then the group presented a more comprehensive account of the synthesis and structural chemistry of half‐sandwich complexes [Ln(AlMe 4 ) 2 (Cp′)] 89 – 91 containing various substituted Cp ancillary ligands. After systematically investigating the effect of metal size, the substituents on the Cp ligand, and the interaction with cocatalysts, the highest stereoselectivities were reported for the systems 90 /B(C 6 F 5 ) 3 ( trans ‐1,4‐: 95.6 %, M w / M n =1.26) and 88 /B(C 6 F 5 ) 3 ( trans ‐1,4‐: 99.5 %, M w / M n =1.18). in toluene at 40 °C.…”
Section: Stereoselective Polymerization Of Conjugated Dienesmentioning
confidence: 99%